Analisis Pengaruh Kualitas Layanan terhadap Tingkat Kepuasan Pengguna Mobile Banking: Studi Kasus pada Jconnect Bank Jatim - Sophia, Elsha; Taufik Bahtera, Novyandri; Findayanti, Nyna; Nila Firnanda, Nashywa (Jurnal Manajemen dan Organisasi, 2025)
The development of digital technology has encouraged the transformation of banking services toward mobile platforms. However, the quality of Bank Jatim's JConnect Mobile service still needs improvement to achieve optimal user satisfaction. This study aimed to analyze the influence of service quality on the satisfaction of JConnect Mobile Bank Jatim users. The aspects of service quality examined include physical evidence, reliability, responsiveness, assurance, and empathy. A quantitative approach was employed, using multiple linear regression and descriptive statistical analysis. The sample consisted of 80 respondents who were JConnect users in the Surabaya area. The results of the study indicated that all service quality variables had a significant influence on user satisfaction. Physical evidence (t-count = 0.041), reliability (t-count = 0.039), responsiveness (t-count = 0.023), assurance (t-count = 0.004), and empathy (t-count = 0.014) were found to have significant partial effects. Simultaneously, the analysis showed a significance value of 0.000, which is lower than the alpha value, indicating that all service quality variables—physical evidence, reliability, responsiveness, assurance, and empathy—collectively had a significant effect on user satisfaction. It can be concluded that service quality is an important factor that determines the satisfaction level of JConnect Mobile Bank Jatim users.